Implementation of Cloud Computing in E-Gizi for Recording and Reporting Toddler Nutrition Status in Batuphat Timur Village via Mobile Applications - Munanda, Allissa; Hidayat, Hari Toha; Safriadi, Safriadi (Politeknik Negeri Lhokseumawe, 2024)
Based on existing data in 2022, Aceh still at the fifth highest level in indonesia for the stunting category. At this time, many posyandu still use books to record children’s growth development and this is very ineffective. Based on this fact, a mobile application is needed that can be used for recording and reporting child growth and development. The reseach aims to produce an application that is effective and can be implemented in the East Batuphat posyandu, so that it make easier for posyandu officiers to record and report child growth and development. This reseach used the blackbox testing method to detemine the level of user satisfaction with the feasibility of the application. The result of testing the feasibility of applications using blackbox testing are 95.8% user satisfaction and 4.2% user dissatisfactions and result based on child data obtained from the East Batuphat health center more than 80% of children are in good nutritional status.